1681 Late-Preterm Delivery: Psychological Distress and Lactogenesis. (October 2012) - Gabrieli, C; Ciullo, R; Sansone, L; Gambina, I; Cavallin, F; Faggian, D; Santini, M; Zanardo, V
Abstract : Late-preterm infants represent the most rapidly growing group of preterm births. The majority of these infants is treated as term neonates at the regular nursery. It is noteworthy that late-preterm infants have a lower breast-feeding prevalence than term neonates. It is not known whether psychological distress affects lactogenesis or the mother-to-infant bonding. The study's aim is to verify if late-preterm delivery is associated to psychological distress affecting Mother-to-Infant bonding and breastfeeding. The study was performed at the Departement of Gynaecology and Human. Reproduction Science of Padua University, between June and October 2011. The study group consisted of 75 mothers: 25 delivered late-preterm with caesarean section and 50 delivered with term vaginal birth. The third day after birth, four psychological tests were administered to mothers: STAI, EPDS, MIBS, LüscherColorTest. Baseline levels of prolactin and cortisol were controlled. ANOVA shows significantly higher levels of trait anxiety and state anxiety in late-preterm infants' mothers:the average trait anxiety is 46.0 (IQR 39.0–50.0) in late-preterm infants' mothers and 40.5 (IQR35.3–44.0) in term infants' mothers (p=0.01); and the average state anxiety is 48.0 (IQR42.0–56.0) in late-preterm infants' mothers and 43.0 (IQR 39.0–48.8) in term infants' mothers (p=0.03) respectively. There are significantly higher levels of depression in late-preterm infants' mothers: in EPDS the average is 9 (IQR 8–13) in late-preterm infants' mothers and 6 (IQR 4–9) in term infants' mothers (p=0.001). In MIBS, joy is lower in late-preterm infants' mothers. In late preterm infants this is associated to reduced exclusive breastfeeding at discharge (20% vs 66%). The LüscherColourTest is comparable for both groups. Mothers who delivered late-preterm have negative emotional changes, without hormonal changes. The psychological distress is negatively associated to an altered Mother-to-Infant bonding and lactation performance.